2006
DOI: 10.1002/mma.743
|View full text |Cite
|
Sign up to set email alerts
|

The 8π‐problem for radially symmetric solutions of a chemotaxis model in the plane

Abstract: SUMMARYThe existence, uniqueness and large time behaviour of radially symmetric solutions to a chemotaxis system in the plane R 2 are studied either for the critical value of the mass equal to 8 or in the subcritical case.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
217
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 134 publications
(227 citation statements)
references
References 14 publications
4
217
1
1
Order By: Relevance
“…Let us observe that for τ > τ * the function M (a, τ ) depends on a in a nonmonotone manner. This is a significant difference with the monotone dependence of self-similar solutions of the parabolic-elliptic Keller-Segel system (see [3,Sec. 4]).…”
Section: Remarkmentioning
confidence: 97%
See 1 more Smart Citation
“…Let us observe that for τ > τ * the function M (a, τ ) depends on a in a nonmonotone manner. This is a significant difference with the monotone dependence of self-similar solutions of the parabolic-elliptic Keller-Segel system (see [3,Sec. 4]).…”
Section: Remarkmentioning
confidence: 97%
“…However, it has not yet been proved that explosion occurs in finite time as soon as M > 8 π, for instance under some additional assumptions like a smallness condition on R R 2 |x| 2 n 0 (x) dx. If M = 8 π, there is an infinite number of steady states (see [3]), but no other result is available, apart from self-similar solutions.…”
Section: Introductionmentioning
confidence: 99%
“…However, there exist solutions having more complicated behavior. In two dimensional case, bounded oscillating solutions and unbounded oscillating solutions were found (see [10]), by using a similar argument to [19] and the stability of stationary solutions shown in [2]. In [19], the following Cauchy problem u t ¼ Du þ u p in R n  ð0; yÞ; uðÁ; 0Þ ¼ u 0 in R n was considered, the existence of bounded oscillating solutions and unbounded oscillating solutions were constructed, and in the proof it is important that each stationary solution is stable and that stationary solutions layer, where n b 11 and p b p JL ¼ fðn À 2Þ 2 À 4n þ 8 ffiffiffiffiffiffiffiffiffiffiffi n À 1 p g=fðn À 2Þðn À 10Þg.…”
Section: Introductionmentioning
confidence: 86%
“…Here, k Á k L p is the standard L p ðR n Þ norm for p A ½1; y . In two dimensional case, it was shown that radial stationary solutions are stable under radial and small perturbations (see [2]), which means that some radial solutions converge to a stationary solution.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation